Mechanisms of iron metabolism in Caenorhabditis elegans - Anderson, Cole P.; Leibold, Elizabeth A. (Frontiers in Pharmacology, 2014)
Iron is involved in many biological processes essential for sustaining life. In excess, iron is toxic due to its ability to catalyze the formation of free radicals that damage macromolecules. Organisms have developed specialized mechanisms to tightly regulate iron uptake, storage and efflux. Over the past decades, vertebrate model organisms have led to the identification of key genes and pathways that regulate systemic and cellular iron metabolism. This review provides an overview of iron metabolism in the roundworm Caenorhabditis elegans and highlights recent studies on the role of hypoxia and insulin signaling in the regulation of iron metabolism. Given that iron, hypoxia and insulin signaling pathways are evolutionarily conserved, C. elegans provides a genetic model organism that promises to provide new insights into mechanisms regulating mammalian iron metabolism.